Agents of chaos : Thomas King Forçade, High Times, and the paranoid end of the 1970s - Howe, Sean (Hachette Books, Hachette Book Group, 2023)
"At the end of the 1960s, the mysterious Tom Forçade suddenly appeared on the scene, insinuated himself into the top echelons of the political counterculture, and took over operations of the Underground Press Syndicate, a coalition of newspapers across the country. Even as he weathered government surveillance and harassment, he embarked on a landmark court battle to obtain White House press credentials. But his outrageous stunts--like pieing Congressional panelists, stealing presidential portraits, and picking fights with other activists--led to charges that he was an agent provocateur. He claimed that he was just trying to "advance international surrealism." As the movements of that decade faded, Forçade saw a new path forward--marijuana, he believed, could be used as a tool for cultural and economic revolution. The goal was simple: what Playboy had done for sex, High Times would do for marijuana, dragging a taboo subject into the mainstream. Bankrolled by drug-dealing profits, the magazine was a travelogue of globe-trotting adventure and a wellspring of news about "the business" from a worldwide network of sources. With regular updates on legislation, advice for would-be entrepreneurs and charts of price fluctuations, the glossy magazine used a distinctly cosmopolitan sensibility that simultaneously legitimized and commodified drug culture. Its editorials--which warned against corporate interests descending upon legalized weed and international drug wars serving as cover for imperialist adventures--would prove to be prophetic. But High Times soon threatened to become nothing more than the "hip capitalism" that he'd railed against for so long, and Forçade felt his enemies closing in. Agents of Chaos is an entertaining, fast-paced tale about attacks on journalism, campaigns of disinformation, governmental secrecy, corporatism, and political factionalism. The tragedies and triumphs of Tom Forçade mirror the cultural transformations of 1970s America, wrought by forces that continue to clash today in the tenuous spaces between unrest, activism, and power"--